Sredstva èkonomnoj peredačy informacii v sovremennoj presse - Komilicyna Margarita A.МАРГАРИТА A. (Stylistyka, 2021)
The article focuses on different active means of compression of utterance and text, employed in modern newspapers writing on socio-political matters. This results in the information in structurally sim ple sen ten ces being presented in condensed fonn with a heavier load of meaning. It appears, that given the choi ce of means of conveying infonnation the preference, as a rule, will be for the structurally simplest, reduced variants and at the same time for the most expressive. The article analyses in detail one of such means - structurally simple sentences whose nominative meaning is derived from severa! propositions. These are called simple polypropositive sentences. Aiming at being closer to the addressee allows modem mass media to actively use colloquia! speech pattems characterised by economy of expression. For instance, joumalists might substitute nominalised structures with concrete proper names requiring the knowledge of context. The influence of colloquia! speech on the language of modem media is fett in the use ofcondensed attributive structures resulting from the transfonnation of a predicative unit into an attributive word combination. Such compressed structures make unusual, highly expressive and often metaphorical utterances, enhancing the impact on the reader. The article also deals with reduced question-answer unities. It is the initial question that is most often reduced and only the author’s reaction to the potentia! opponent’s question is given. As a rule, it is in the form of an ordinary disagreement masked as agreement. Authorising structures are also used. Instead of a full predicative unit naming the source of infonnation and the way it was got, joumalists might opt for condensed structures with deverbatives, that are included into the sentence as an introductory component. Economically effective in the media are also precedent phenomena that allow to compress the text by references to the background knowledge of mass addressee. Metaphors might also be included here as condensed comparisons. The article also analyses pragmatic functions of inverted commas which help to implicitly express objective and some subjective meanings of the utterance and whole text passages.